ChemInform Abstract: Antibacterial Action of Quinolones: From Target to Network. Issue 42 (1st October 2013) - Cheng, Guyue; Hao, Haihong; Dai, Menghong; Liu, Zhenli; Yuan, Zonghui
Abstract Review: 99 refs.